MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM MEMPENGARUHI MOTIVASI GURU DI LEMBAGA PENDIDIKAN ISLAM BANI HASYIM - Qurroti A'yun (VICRATINA, 2019)
Changes to the needs of the development of science and technology required management of educators and educational staff in order to improve the quality of education. In the Bani Hasyim educational institution the motivation of teachers is one of the bases in raising teachers to improve performance in building the nation's generation. The study uses qualitative interpretive paradigm. Teachers at the Bani Hasyim educational institution have 2 types of motivation, namely responsibility motivation and worship motivation. Motivation of responsibility shapes the belief in the teacher that the profession as a teacher is not just transferring knowledge but rather the transfer of personality. Motivation of worship, is a belief in spiritual values that underlies devotion to the profession. The understanding of worship and responsibility as a form of teacher professionalism leads to spiritual values. Keywords: management, educators and education personnel, teacher motivation